Improving wheat yield and water use efficiency through soil water-guided furrow irrigation and hydraulic simulation - Dong-Hyeon Kim; Younggu Her; Liguang Cheng; Taeil Jang (Agricultural Water Management)
Despite the increasing adoption of precision irrigation technologies including drip and sprinkler systems, traditional methods such as furrow irrigation remain widely used among small-scale farmers due to their lower costs and simpler management requirements. However, limited research has focused on improving the efficiency of furrow irrigation, which holds significant potential for enhancing water use efficiency and agricultural productivity, particularly in regions prone to drought and flood. This study evaluates the impact of precise furrow irrigation on wheat growth under two soil water content-based irrigation schedules, one based on available soil water and the other on saturation water content. These outcomes were compared with those under rainfed conditions. This study combined field monitoring and hydraulic modeling to evaluate how different irrigation depths and furrow geometries affect water distribution uniformity and crop yield. The results demonstrated that soil water content-based irrigation can improve wheat yield and water use efficiency compared to rain-fed conditions. However, hydraulic modeling revealed that ridge-based soil water monitoring may underestimate actual water demand, as it overlooks water losses between the ridge and the furrow. The modeling also showed that parabolically shaped furrows achieved the highest distribution uniformity (DU). Interestingly, saturation-based irrigation scheduling yielded the highest DU. However, this approach caused waterlogging and reduced yields, suggesting that high DU does not necessarily lead to optimal crop performance. These findings underscore the limitations of relying solely on DU for irrigation scheduling decisions. Overall, the study highlights the potential of soil water content-based irrigation strategies, particularly one using available water content thresholds, to improve both water use efficiency and crop productivity. These insights contribute to the development of practical and effective water management guidelines for furrow-irrigated agricultural systems.